Dependence of Electrical Conductivity on Phase Morphology for Graphene Selectively Located at the Interface of Polypropylene/Polyethylene Composites - Ce Tu; Kenji Nagata; Shouke Yan (Nanomaterials, 2022)
Conductive composites of polypropylene (PP) and polyethylene (PE) filled with thermally reduced graphene oxide (TRG) were prepared using two different processing sequences. One was a one-step processing method in which the TRG was simultaneously melt blended with PE and PP, called TRG/PP/PE. The second was a two-step processing method in which the TRG and the PP were mixed first, and then the (TRG/PP) masterbatch was blended with PE, called (TRG/PP)/PE. The phase morphology and localization of the TRG in TRG/PP/PE and (TRG/PP)/PE composites with different PP/PE compositions were observed by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The TRG was found to be selectively dispersed in the PE phase of the TRG/PP/PE composites, resulting in a low percolation threshold near 2.0 wt%. In the (TRG/PP)/PE composites, the TRG was selectively located at the PP/PE blend interface, resulting in a percolation threshold that was lower than 1.0 wt%. With the addition of 2.0 wt% TRG, the (TRG/PP)/PE composites exhibited a wide range of electrical conductivities at PP/PE weight ratios of 10 w/90 w to 80 w/20 w. Moreover, electrical and rheological measurements of the composites revealed that the co-continuous phase structure is the most efficient candidate for the fabrication of conductive composites.